2015
DOI: 10.1001/jamaoto.2015.1323
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Patient-Level Risk Factors for 30-Day Readmissions Following Free Tissue Transfer for Head and Neck Cancer

Abstract: In this study, advanced pathologic tumor staging and tumor location were associated with 30-day readmissions in patients with head and neck cancer who receive free flaps. Our results provide a benchmark for risk stratification that can be used in system-based practice improvements, health care cost savings, and postoperative patient counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
72
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(84 citation statements)
references
References 27 publications
11
72
1
Order By: Relevance
“…Due to the nature of the CDB/RM, readmissions to another hospital cannot be counted toward the index hospital readmission rate. Other studies report 30‐day readmission rates in the order of 3.2% to 14.5% . Despite this, the 7‐ and 30‐day readmission rates for geriatric patients (1.10%–1.75% and 3.84%–5.44%, respectively), when compared to previous studies for younger patients (1.55%–2.63% and 5.11%–6.76%, respectively) show that it is not that different.…”
Section: Discussionmentioning
confidence: 69%
“…Due to the nature of the CDB/RM, readmissions to another hospital cannot be counted toward the index hospital readmission rate. Other studies report 30‐day readmission rates in the order of 3.2% to 14.5% . Despite this, the 7‐ and 30‐day readmission rates for geriatric patients (1.10%–1.75% and 3.84%–5.44%, respectively), when compared to previous studies for younger patients (1.55%–2.63% and 5.11%–6.76%, respectively) show that it is not that different.…”
Section: Discussionmentioning
confidence: 69%
“…Dziegielewski et al also reported a 7.3% 30‐day readmission rate among all otolaryngology patients at their institution; however, when stratified by low‐ and high‐risk procedures, they found lower and higher 30‐day readmission rates, respectively. More complex procedures, such as head and neck oncologic surgery, are associated with a higher risk of 30‐day readmission . Unplanned 30‐day readmission rates following free tissue transfer can range from 7.9% to 11.6% .…”
Section: Discussionmentioning
confidence: 99%
“…Our study is not the first study to evaluate risk factors for re-admission in head and neck cancer patients. In multiple studies, wound complications such as fistula or infection are among the most common reasons for readmission, with an estimate of 51% of re-admissions being related to complications [14,15,18]. Advanced tumor stage (T3-T4) as well as longer length of stay have also been found to be predictors re-admission [13,18].…”
Section: Discussionmentioning
confidence: 99%
“…In multiple studies, wound complications such as fistula or infection are among the most common reasons for readmission, with an estimate of 51% of re-admissions being related to complications [14,15,18]. Advanced tumor stage (T3-T4) as well as longer length of stay have also been found to be predictors re-admission [13,18]. Interestingly, the presence of a G-tube at discharge was found to have a 3-fold increase in the rate of re-admission, and was also found to predict re-admission for pneumonia [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation